2001
DOI: 10.1002/1520-6629(200101)29:1<29::aid-jcop3>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Sense of community referred to the whole town: Its relations with neighboring, loneliness, life satisfaction, and area of residence

Abstract: The aim was to explore the relationships between sense of community and various factors with respect to a fairly broad area (town, city, or large quarter of a metropolis). Degree of neighboring, life satisfaction, loneliness, and area of residence were also considered. Subjects included 630 men and women, aged 20‐65 years, with different educational levels. They were individually administered a sociodemographic questionnaire, the Italian Sense of Community Scale, the Satisfaction with Life Scale, the Universit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
231
4
16

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 316 publications
(266 citation statements)
references
References 36 publications
15
231
4
16
Order By: Relevance
“…Neighboring provides a means by which residents can establish social connections that may occur at an individual or neighborhood level (Lochner et al 1999). In a study of 630 neighborhood residents in Italy, Prezza et al (2001) found neighborhood relations to be more strongly associated with sense of community compared to other neighborhood and demographic variables, including years of residence, area of residence, and marital status. Frequency of neighboring behavior has also been found to explain increased sense of community and ''rootedness'' in the neighborhood in a study of 345 residents living in nonapartment dwellings in Winnipeg, Canada (Farrell et al 2004).…”
Section: Neighbor Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neighboring provides a means by which residents can establish social connections that may occur at an individual or neighborhood level (Lochner et al 1999). In a study of 630 neighborhood residents in Italy, Prezza et al (2001) found neighborhood relations to be more strongly associated with sense of community compared to other neighborhood and demographic variables, including years of residence, area of residence, and marital status. Frequency of neighboring behavior has also been found to explain increased sense of community and ''rootedness'' in the neighborhood in a study of 345 residents living in nonapartment dwellings in Winnipeg, Canada (Farrell et al 2004).…”
Section: Neighbor Relationsmentioning
confidence: 99%
“…Sense of community (SOC) has been linked to increased psychological well-being (Pretty et al 1996b;Prezza et al 2001), perceptions of belonging and community connectedness (Sonn and Fisher 1996), and participation in the community . Sense of community has been investigated and argued to be relevant for diverse populations, ranging from school-age children and urban neighborhood residents to indigenous Australians and Latin American residents in Caracas (e.g., Garcia et al 1999;McMillan and Chavis 1986;Perkins et al 1990;Pretty et al 1996a;Sonn 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The salient relationship between sense of community and life satisfaction is supported by Prezza and colleagues (Prezza, Amici, Roberti, & Tedeschi, 2001;Prezza & Costantini, 1998), particularly regarding smaller communities. The relationship between health and life satisfaction also has been heavily documented (Diener, 1984;.…”
Section: Prediction Of Life Satisfactionmentioning
confidence: 92%
“…Similarly, decreased levels of work-family conflict [1,37] and domestic labour [31], increased quality time with family and friends [32,53], and strong sense of belonging to community tend to improve social contact and life satisfaction [50].…”
Section: Intervenining Conceptsmentioning
confidence: 99%